A comparison between two therapeutic methods in solving mathematical problems for students of the College of Basic Education (Journal of the College of Basic Education, 2022)
Mathematics is an important science because of its contributions to scientific and technical developments as well asOn its role in developing talents and intuition, which is one of the oldest sciences known to man, given his needto her in the process of counting and measuring, and (Bell (1986) called her the Queen of Science because of her great connection withwith all other branches of knowledge. (Bill (1986, 22) (1) Mathematics is one of the basic componentscurriculum at all stages.